Association among basal metabolic rate, body composition and pulmonary function in university students - Myat, Su Bo; Cheah, Whye Lian; Nur Adriana, Azhar; Muhammad Ashraf Fraiee, Amran; Xin, Yeo Deng; Nurazizah, Anis (2021)
Background: Variation in basal metabolic rate (BMR) has been closely related to obesity and pulmonary function. Objectives: To determine the association between BMR, body composition and pulmonary function among university students aged 19 - 22 years old. Methods: This cross-sectional study was carried out among the pre-clinical students of the Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak. Data was collected using questionnaire, anthropometric measurement, and spirometer. Statistical analysis was performed using IBM SPSS version 20.0. Results: A total of 230 respondents participated in this study. There were 47.7% males and 41.1% females who were overweight and obese, 40.3% of the males and 46.0% of the females had high percentage of body fat, and 22.4% of the male respondents had high and very high visceral fat compared to 7.4% of the female respondents. BMR and force vital capacity (FVC) values were significant higher for males than females. Multivariate analysis showed that after adjusted for gender, percentage of visceral fat (adjust β = 0.620, 95% CI = 24.436 - 32.738), and FVC (adjust β = 0.152, 95% CI = 19.762 - 49.038) were significant associated with BMR. Conclusions: Visceral fat has a stronger effect on BMR compared to body fat and FVC. Body fat, visceral fat and pulmonary function were found to be significantly associated with BMR, with visceral fat the highest effect on BMR. Understanding the association of these variables help in the intervention of obesity among young adults.